Instant Salam: an Instant Antidiarrheal Drink Based on Snedds of Salam Leaf Water Extract Syzygium polyanthum (Wight) Walp Against Salmonella typhimurium - Celia Shine Chandra; Eve Maydelline Gunawan; Endang Natalya (Green Publisher Indonesia, 2026)
Syzygium polyanthum (Wight) Walp as known as bay leaves are traditionally used to treat various diseases such as diabetes mellitus, gastritis, ulcers, diarrhea, and skin diseases, but there is not enough research that discusses the benefits of this. This study aims to test the antidiarrheal content of instant drinks made from bay leaves as an alternative treatment for typhoid symptoms, reduce the reluctance of children and the elderly to take medication, reduce the risk of conventional antibiotic resistance that occurs due to continuous use of antibiotics, and utilize Indonesia's natural wealth as an alternative antibacterial agent accompanied by flexibility with the sophistication of the times, namely by the use of nanotechnology, one of which is called nanoemulsion. The manufacture of instant bay leaf nanoemulsion drinks involves a SNEDDS base solution that is homogenized with ultra turrax at 10,000 rpm for 30 minutes before being sonicated for 15 minutes at 40°C. The results showed that Salam Instant drink has antibacterial activity in the form of MIC of 0.781 mg/ML, MBC 0.156 mg/mL, DZI 1.775 ± 0.101 mm, inflammatory protection 76.04 ± 2.751%, antidiabetic 151.91 ± 4.8 IC50 ug/mL. From the characterization of bay leaf SNEDDS, an average PSA of 680.057 ± 43.598 um, Zeta potential -5.08 ± 0.473 mV was obtained. Based on the results obtained, it can be concluded that SNEDDS-based bay leaf instant drink has antidiarrheal activity against diarrhea symptoms due to Salmonella typhimurium infection and has the potential to be used as an alternative medicine for diarrhea.